Perubahan Fungsi Spasial sebagai Akibat Perkembangan Pariwisata di Banjar Kedungu, Desa Belalang Kecamatan Kediri, Kabupaten Tabanan - Rapiana, I Putu Edy (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 4 No 1 (2017): April 2017, 2017)
Tourism has largely contributed to the development of Bali Island. To mention a few, it creates job opportunities; increases income per capita; encourages migration, and is also a powerful stimulant for land use change. Taken the latter as a context to its focus and spatial developments taken place in Banjar Kedungu, Belalang Village, Kediri District of Tabanan Regency as its case study, this article addresses three issues, including 1) forms of land use changes; 2) how each land use change occurred; and 3) determining factors that influence land use changes. This study applied a cross-disciplinary conceptual framework composed by the theory of change, a series of concepts in regard to spatial development, and the theory of commodification. It also implemented a combined qualitative-quantitative research approach. Data presented within was collected by conducting physical observation and in depth interview with potential informants. Main study findings show there is a tendency for land use change to move to the southern part of Kedungu. It is mainly due to change in legal land ownership. Many landowners decided to sell their agricultural land either for economic reason or having to migrate to a different part of the neighborhood or to new places outside their community. Further reasons for land use changes is explained in detail within, which are categorized in two major groups of internal and external factors. Keywords: change, function, spatial, tourism, Banjar Kedungu